Does Pop Culture Trend Drives Brand Awareness on Purchase Intention? A Case Study of the Squid Game Movie Series on Dalgona Candy - Rachmanda Putri, Marsha; Aprianingsih, Atik; Imran, Jovanska Arfianda; Aminuddin, Rahmat Ridlo (Journal Integration of Management Studies, 2023)
This study investigated the inclination between the pop culture trend of squid game movies to Dalgona candy purchase intention. The statistical population includes millennials familiar with Korean drama and those who watched the Squid Game movie series in particular. 130 people were selected by random sampling to respond to a research questionnaire. Variables were analyzed by multiple regression analysis using validity and reliability measurement through Cronbach's alpha from SPSS and RStudio to find the intercept between brand awareness and trend theory variables. Findings stated that both variables positively impact Dalgona Candy Purchase Intention. However, The variable of Trend Theory does not have a significant impact on Dalgona Candy Purchase Intention. Meanwhile, brand awareness is not the key to purchase intention despite having a positive effect.